Balustrades, David Sassoon Clocktower - Ghosh, Ayan (2023)
The clock tower is built in Neo-Palladian style, named after Andrea Palladio (1508-1580). Palladio was inspired by concepts of symmetry, perspective, and classical forms inspired by ancient Roman and Greek architecture. Hence, Palladian architecture has a resemblance to Italian Renaissance architecture, as a conscious revival was made to incorporate elements of ancient Greek and Roman thought and material culture.